Some personnel transactions affecting shop teachers in selected state colleges of technology in the Philippines - Boonpange, Thiravath 1946- ([Quezon City s.n.], 1974)
This study analyzed personal policies and practices regarding shop instructors in the Bulacan College of Arts and Trades, Philippine College of Arts and Trades, Tarlac College of Arts and Trades, and Central Luzon Polytechnic College. The 159 shop instructors are paid salaries equal to those of academic instructors using the WAPCO or the institutional salary scales. They enjoy privileges, fringe and other benefits similar to those enjoyed by academic instructors including vacation and sick leaves to those who regularly perform administrative and supervisory functions, maternity leave, military leave, insurance with the GSIS, and Medicare benefits. The maximum teaching load is 30 hours/week.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Technical education -- Philippines